Afterload‐induced left ventricular diastolic dysfunction during myocardial ischaemia and reperfusion. Issue 3 (2nd February 2015) - Diakos, Nikolaos A.; Pozios, Iraklis; Katsaros, Lampros; Vakrou, Styliani; Sventzouri, Stefania; Michelinakis, Nikolaos; Tseliou, Eleni; Bonios, Michael; Malliaras, Konstantinos; Papalois, Apostolos; Anastasiou‐Nana, Maria; Terrovitis, John V.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? While the load dependence of the diastolic function is established for the normal heart, little is known about the response of the acutely ischaemic and reperfused myocardium to alterations in afterload. What is the main finding and its importance? Using a model that simulates the clinical scenario of acute ischaemia–reperfusion, we show that increased afterload aggravates diastolic dysfunction during both acute ischaemia and reperfusion. In addition, increased afterload induces diastolic dyssynchrony, which might be the underlying mechanism of the diastolic dysfunction of the ischaemic myocardium. These findings provide us with new information regarding how better to manage patients who undergo revascularization therapy after acute myocardial infarction. The effects of changes in left ventricular (LV) afterload on diastolic function of acutely ischaemic and reperfused myocardium have not been studied in depth. We examined the following factors: (i) the consequences of increasing the LV afterload on LV diastolic function during acute ischaemia and reperfusion; (ii) whether the myocardial response to afterload elevation is stable throughout a 2 h reperfusion period; and (iii) the role of LV wall synchrony in the development of afterload‐induced diastolic dysfunction. We instrumented 12 anaesthetized, open‐chest pigs with Millar pressure catheters and piezoelectric crystals before ligating mid‐left anterior descending coronary artery for 1 h, followed by reperfusion for 2 h. Six of the animals survived throughout the 2 h of reperfusion, and their data were used for comparisons across the different experimental phases. Left ventricular afterload was increased by inflating an intra‐aortic balloon. Data were recorded at baseline, after 20 min of coronary occlusion and at 30 and 90 min of myocardial reperfusion. The increased afterload for 2 min lengthened the isovolumic relaxation during ischaemia and during early and late reperfusion but had no significant effect on isovolumic relaxation before coronary artery occlusion. Increasing the afterload aggravated LV diastolic dyssynchrony during coronary artery occlusion, but not during reperfusion. The afterload‐induced prolongation of isovolumic relaxation was positively correlated with afterload‐induced diastolic dyssynchrony. These observations indicate that, during myocardial ischaemia and throughout reperfusion, LV diastolic function is afterload dependent. Afterload‐induced diastolic dyssynchrony might be an underlying mechanism of diastolic dysfunction during acute ischaemia.